Analisis Sektor Basis (Sektor Unggulan) dan Ketimpangan Pendapatan di Provinsi Banten pada masa Pandemi Covid-19 Base Sector Analysis (Leading Sector) and Income Inequality in Banten Province during the Covid-19 Pandemic - Mangara, Togi Haidat; Simanungkalit, Erlandy Lasproito; Syaifudin, Rizal; Desmawan, Deris (Universitas Labuhanbatu, 2024)
The outbreak of the Covid-19 pandemic has resulted in changes in the world's life order and has become a big challenge for the world, as well as in terms of the economy. Many sectors experienced a decline which resulted in income inequality occurring. This study aims to analyze the leading/base sector and analyze its relationship to income inequality during the Covid-19 period in Banten Province. The research method used is Location Quotient (LQ) and Shift Share Analysis to determine the base/leading sector, and to analyze income inequality using panel data regression. The results of this study indicate that the results of the calculation of the Location Quotient (LQ) of the base sector or leading sector during the Covid-19 pandemic, there were no significant changes which were still outperformed by the mining and quarrying sector, which was followed by the agriculture, forestry, and mining sectors. fishery. The results of the Shift Share Analysis calculation show that the leading sector during the Covid-19 pandemic was outperformed by the manufacturing industry sector, followed by the construction sector and other sectors that affected the total indicators of activity and regional economic growth both from the influence of national growth, proportional growth, and share growth. region. Statistically, the regional gross domestic product per capita and the minimum wage have a positive value, but are not significant for income inequality in the province of Banten, and the human development index variable is negative. Partially there is no influence between the independent variables on the dependent variable, but simultaneously there is a significant effect between the independent variables on the dependent variable, and there is a strong relationship between the independent variables and the dependent variable.